Thromboprophylaxis in Hospitalized Non-Critically Ill Patients With Mild-to-Moderate COVID-19 Infection: A Systematic Review and Meta-Analysis - Awatif Hafiz PharmD, BCCP; Hadeel Alkofide PhD; Khalid Al Sulaiman BCCCP, BCNSP, MBA, FCCM; Hala Joharji PharmD, BCPS, BCMTM; Sarah Aljohani PharmD, BCPS; Khadijah A. Sarkhi PharmD; Reem Alharbi PharmD; Ghazwa B. Korayem PharmD, BCPS; Mashael AlFaifi PharmD, BCPS; Samiah Alsohimi PharmD; Ohoud Aljuhani PharmD (Clinical and Applied Thrombosis/Hemostasis, 2023)
The prevalence of venous thromboembolism is high in patients with COVID-19, despite prophylactic anticoagulation. The evidence that supports the preferred thromboprophylaxis regimen in non-critically ill patients with mild to moderate COVID-19 is still limited. Therefore, this systematic review and meta-analysis aimed to compare the clinical outcomes of hospitalized patients with mild to moderate COVID-19 who received standard thromboprophylaxis anticoagulation with intermediate to high prophylaxis regimens. We systematically searched MEDLINE and Embase databases for published studies until August 17th, 2022. We included studies on patients with mild to moderate COVID-19 who received thromboprophylaxis during their hospital stay. Patients who received standard prophylaxis dose “control group” were compared to patients who received intermediate to high prophylaxis “intervention group”. Random effect models were used when pooling crude numbers and adjusted effect estimates of study outcomes. A comprehensive analysis was conducted, encompassing seven studies involving a total of 1931 patients. The risk of all-cause thrombosis was not statistically different between the two groups (risk ratio [RR] 1.48, 95% confidence interval [CI] [0.11, 20.21]). The risk of minor bleeding was reported to be lower in patients who received intermediate to high prophylaxis (RR 0.64, 95% CI 0.21, 1.97), while had a higher risk of major bleeding compared with the standard prophylaxis (RR 1.40, 95% CI 0.43, 4.61); however, did not reach the statistical significance. The overall risk for all hospital mortality favored the utilization of intermediate to high doses over the standard thromboprophylaxis dosing (RR 0.47, 95%CI 0.29, 0.75). In medically ill patients with COVID-19, there is no difference between standard and intermediate to high prophylaxis dosing regarding thrombosis and bleeding. However, it appears that intermediate to high prophylaxis regimens are linked to additional survival benefits.